Case Report: First Report of T-Cell Large Granular Lymphocytic Leukemia With NPL-DHX9 Gene Fusion Successfully Treated With Cladribine: Clinical Experience and Literature Review - Hu, Qin; Li, Yunfei; Zhang, Ying; Sun, Shusen; Wang, Hui; Jiang, Zhiping; Deng, Sheng (Frontiers in Oncology, 2022)
Background T-cell large granular lymphocytic leukemia (T-LGLL) is a rare lymphoproliferative disorder that starts in T cells and is usually indolent. Long-term use of immunosuppressants, combined with agranulocytosis, is a double-edged sword, as both can lead to serious infections, especially in patients with combined hematologic malignancies and immune defects. Case presentation A 30-year-old female patient was admitted to the hospital because of agranulocytosis for five years, with chest tightness, fatigue, and fever for two days. Pathology and metagenomic next-generation sequencing (mNGS) detected Aspergillus. Although she received cyclosporine and methylprednisolone, the patient showed drug intolerance and progression with invasive pulmonary fungal infections. After a bone marrow aspiration biopsy and other related examinations, she was diagnosed with T-LGLL and invasive pulmonary aspergillosis (IPA). T-cell immunophenotype was CD45+CD3dim+CD5-CD4-CD8+CD7+CD57p+CD25-CD30-, TCRγδ+, transducer and activator of transcripton-3 (STAT3) Y640F mutation and fusion gene NPL-DHX9 rearrangement were confirmed, which has never been reported in hematological diseases. After voriconazole regimen adjustment during treatment based on therapeutic drug concentration monitoring (TDM) and improvement in lung infection, the patient finally treated with purine nucleoside analogues (PNA) cladribine as a single agent at 0.14 mg/kg/d for 5 days. Complete response was achieved after four-cycles cladribine treatment (WBC 2.1*109/L, HGB 117 g/L, PLT 196*109/L, ANC 1.6*109/L, and ALC 0.2*109/L). Conclusions To our knowledge, this is the first case of T-LGLL with a rare γδ type and fusion gene NPL-DHX9 rearrangement. The patient was successfully treated with cladribine, suggesting that this regimen could be a promising therapeutic strategy for patients with aggressive T-LGLL.